Optimization of solid waste collection system in a tourism destination - C. Le Dinh; T. Fujiwara; M. Asari; S.T. Pham Phu (Global Journal of Environmental Science and Management, 2022)
BACKGROUND AND OBJECTIVES: Prior to the COVID-19 pandemic, Hoi An City was one of the most famous tourist destinations in the world. This led to a rapid increase in solid waste generation, leading to problems and challenges in solid waste collection and management. This problem is also being experienced by other developing countries of the world. Despite the existence of established waste management strategies, targets set for the collection of recyclable waste have not been met. This study introduces solutions to the problems and challenges faced by the waste management sector in Hoi An city and other developing countries. This study aimed to i) optimize the map of the recovery recycling stations in an urban community, ii) develop an effective solid waste collection system, and iii) provide management tools to enhance recycling activities, contributing to improving waste management in Hoi An city.METHODS: The RRSs were integrated into a solid waste collection system in the urban communities of Hoi An City, were conducted through location-allocation analysis in a geographic information system environment. Routing problems of carts were solved in the combination of the rescheduling of existing solid waste collection activities in the study site. The economic evaluation by scenarios was also calculated for ten years to assess the feasibility of scenarios.FINDINGS: Thirty-four locations were identified and optimized to accommodate the RRSs and new collection routes. The distances travelled and working time increased in proportion to the increase in waste separation effectiveness. Waste separation is vital to the effectiveness of the new solid waste collection system. The optimal solid waste practice model (in scenarios 2 and 4) revealed the positive results in improving the solid waste collection system, operating economy, and local adaptation.CONCLUSION: This study redesigned the solid waste collection system to solve the current problems in the tourism destination of Hoi An city. This study contributed as a case study of integrating urban recovery recycling stations into optimizing a solid waste collection system in a tourism destination. Introducing strict waste separation was the pivotal first step in systematically upgrading the solid waste collection system in Hoi An City. This study’s findings provide government officials and service providers with methods that can be applied to solve the problems faced by Hoi An city's existing solid waste collection and management system.